AN ANALYSIS OF THE QUANTITY OF ZINC AND INTERFERON-GAMMA IN THE SERUM OF INDIVIDUALS SUFFERING FROM CUTANEOUS LEISHMANIASIS IN THE CITY OF SALADIN RUNNING TITLE : QUANTITY OF ZINC AND INTERFERON-GAMMA IN THE SERUM OF INDIVIDUALS SUFFERING STATUS IN CUTANE - Al-Gburi, Khatab O, Rebai, Ahmed (Chelonian Research Foundation, 2023)
Summary Zinc is one of the most essential cytokines because it plays a role in the proliferation of cells and tissues and also plays an active part in the body's immune system. Zinc also plays a role in the production of antibodies. In addition to being one of the most important cytokines, kama-interferon is noteworthy since it is an essential component of the immune system that is found in the human body. The objective of this study was to first assess how high the levels of gamma-interferon and zinc were in the blood serum of patients who had been diagnosed with cutaneous leishmaniasis and then compare those levels to the levels that were discovered in the control groups. 48 people with cutaneous leishmaniasis were taken during the time period of October 2020 to the end of September 2021 in the dermatology department of the outpatient clinic in Tikrit Teaching Hospital. The percentage of males was 61, which is equivalent to 60.39%, and the percentage of females was 40, which is equivalent to 39.60%. They ranged in age from one year old all the way up to 71 decades old. The youngest was one year old A spectrophotometer was used to assess the mean concentration of zinc in the serum of all patients with cutaneous leishmaniasis as well as in the serum of control groups. The results of this measurement were compared with one another. The mean concentration of zinc in patients with cutaneous leishmaniasis was found to be 9.6 mmol/L, while in the control groups of those aged 15 years and below, it was 11.4 mmol/L. In males with cutaneous leishmaniasis, the average zinc concentration was 10 mmol/L, whereas in the control groups, it was 11.6 mmol/L. The average zinc content in females with cutaneous leishmaniasis was 9.4 mmol/L, whereas the percentage was significantly higher in the control group, reaching 10.8 mmol/L In addition, the findings of the research indicated a statistically signifi cant increase in the concentration of gamma-interferon compared with the groups61control (1P0.01) for those aged 15 years and below, where the rate of gamma-interferon in patients was (0.8) unit/ml and in the control groups (0.5) unit/ml, as well as for those aged mor than 15 years, where the rate of gamma-interferon in patients was (0.8 Where the rate of interferon-gamma in males was (1.1) units/ml while in the control groups it was just (0.6) units/ml. In a similar fashion, the average concentration of gamma-interferon in female patients was (0.7) alone/ml, whereas the average concentration in control groups was (0.5) alone/ml